1994
DOI: 10.1001/archpsyc.1994.03950020063007
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Validity of an Animal Model of Deficient Sensorimotor Gating in Schizophrenic Patients

Abstract: Psychiatric researchers need specific animal models to better understand the neurobiology of schizophrenia. Prepulse inhibition (PPI), the reduction in startle produced by a prepulse stimulus, is diminished in schizophrenic patients. Theoretically, deficient PPI in schizophrenic patients reflects a loss of sensorimotor gating that may lead to sensory flooding and cognitive fragmentation. In rats, PPI is disrupted by systemic administration of dopamine agonists or by manipulations of neural circuitry linking th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

21
380
0
3

Year Published

1998
1998
2007
2007

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 677 publications
(404 citation statements)
references
References 67 publications
21
380
0
3
Order By: Relevance
“…The original dopamine model focused primarily on testing the ability of antipsychotic drugs to block the PPI-disruptive effects of apomorphine in rats (Swerdlow et al, 1994). In sum, these effects of apomorphine in rats are reliably prevented by virtually all antipsychotics that have appreciable affinity for dopamine D 2 receptors.…”
Section: The Dopamine Prepulse Inhibition Model In Ratsmentioning
confidence: 99%
See 1 more Smart Citation
“…The original dopamine model focused primarily on testing the ability of antipsychotic drugs to block the PPI-disruptive effects of apomorphine in rats (Swerdlow et al, 1994). In sum, these effects of apomorphine in rats are reliably prevented by virtually all antipsychotics that have appreciable affinity for dopamine D 2 receptors.…”
Section: The Dopamine Prepulse Inhibition Model In Ratsmentioning
confidence: 99%
“…In sum, these effects of apomorphine in rats are reliably prevented by virtually all antipsychotics that have appreciable affinity for dopamine D 2 receptors. Swerdlow et al (1994) have shown an excellent correlation between the clinical potency of an antipsychotic and its ability to block the PPIdisruptive effects of the dopamine agonist apomorphine in rats. Although this finding provides important validation of the predictive validity of the dopamine PPI model for antipsychotic drugs, it primarily reflects the importance of dopamine D 2 antagonism in antipsychotic drug action and therefore only recapitulates in a behavioral paradigm what was already known from simple ligand-binding assays.…”
Section: The Dopamine Prepulse Inhibition Model In Ratsmentioning
confidence: 99%
“…PPI has been found to be abnormal in schizophrenia patients and in their relatives, and appears to be under significant genetic control (Braff and Geyer, 1990;Cadenhead et al, 2000;Anokhin et al, 2003;Kumari and Postma, 2005;Hong et al, 2007). PPI has increasingly been used as a surrogate index of psychosis in animal models (Swerdlow et al, 1994;Braff et al, 2001). However, PPI abnormality is not specific to schizophrenia or psychosis since it is also associated with several other psychiatric conditions including stress, bipolar disorder with psychotic features, panic disorder, obsessive-compulsive disorder, dementia, and autism (Grillon and Davis, 1997;Perry et al, 2001Perry et al, , 2007Ludewig et al, 2002;Hoenig et al, 2005;Ueki et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…PPI of the ASR is an attenuation of the startle amplitude by a non-startling prepulse preceding the startle-eliciting pulse by a certain amount of time, and is considered an operational measure of sensorimotor gating (eg Graham, 1975;Geyer et al, 1990;Swerdlow et al, 1994). Habituation is a reduction over time of the amplitude of the ASR, seen after repeated presentation of identical startle eliciting pulses, which is not a result of sensory adaptation or muscle fatigue, and is considered a form of non-associative learning (Christoffersen, 1997).…”
Section: Introductionmentioning
confidence: 99%